The collapse of mechanism and the rise of sensibility science and the shaping of modernity, 1680-1760 - Gaukroger, Stephen (Oxford : Oxford University Press, 2010)
How did we come to have a scientific culture - one in which cognitive values are shaped around scientific ones? Stephen Gaukroger presents a rich and fascinating investigation of the development of intellectual culture in early modern Europe, a period in which understandings of the natural realm began to fragment.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Science -- Europe -- History -- 17th century; Science -- Europe -- History -- 18th century; Philosophy and science -- Europe -- History -- 17th century; Philosophy and science -- Europe -- History -- 18th century; Religion and science -- Europe -- History -- 17th century; Religion and science -- Europe -- History -- 18th century; Science and civilization